Product Quality Improvement through Effective Operational Management - Herison, Roni; Halim, Muh.Rizal; Mattalata, Solihin (Bata Ilyas Educational Management Review, 2024)
This study aims to investigate the impact of advanced operational management practices on product quality improvement. It focuses on the integration of Industry 4.0 technologies, Lean Manufacturing principles, and Total Quality Management (TQM) methodologies to enhance operational efficiency and product quality. The study employs a mixed-methods approach, combining quantitative data from structured surveys and qualitative insights from semi-structured interviews. The sample includes manufacturing firms of various sizes, and data analysis involves statistical techniques and thematic analysis to provide a comprehensive understanding of the practices and their effects. The findings reveal that integrating Industry 4.0 technologies, such as IoT and AI, significantly enhances real-time monitoring and control, leading to proactive quality management. Lean Manufacturing principles reduce waste and optimize processes, while TQM fosters a culture of continuous improvement and employee involvement. These practices collectively improve operational efficiency and product quality. The study also identifies the importance of a supportive organizational culture and robust supplier quality management. The study offers practical insights for organizations aiming to enhance product quality through advanced operational practices. It highlights the need for a holistic approach integrating technological advancements with human factors. Despite its contributions, the study's limitations include a focus on manufacturing firms and reliance on self-reported data, suggesting future research should explore broader industry contexts and longitudinal effects to build on these findings.